2012
DOI: 10.1124/mol.112.079319
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Modulation of Endogenous Metabolites as an Avenue for Drug Discovery

Abstract: G protein-coupled receptors (GPCRs) are the largest family of cell surface receptors and a key drug target class. Recently, allosteric drugs that can cobind with and modulate the activity of the endogenous ligand(s) for the receptor have become a major focus of the pharmaceutical and biotechnology industry for the development of novel GPCR therapeutic agents. This class of drugs has distinct properties compared with drugs targeting the endogenous (orthosteric) ligand-binding site that include the ability to sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 31 publications
6
89
0
2
Order By: Relevance
“…To confirm that this cooperativity was not probe dependent, we also examined the allosteric modulation of the GLP-1 metabolite, GLP-1(9-36)NH 2 ( Fig. S11) (36). These data demonstrate that the allosteric modulation of the GLP-1R occurs within a single monomeric unit and does not require dimerization of the receptor.…”
Section: Allosteric Modulation Of the Glp-1r Occurs Within A Single Rmentioning
confidence: 84%
“…To confirm that this cooperativity was not probe dependent, we also examined the allosteric modulation of the GLP-1 metabolite, GLP-1(9-36)NH 2 ( Fig. S11) (36). These data demonstrate that the allosteric modulation of the GLP-1R occurs within a single monomeric unit and does not require dimerization of the receptor.…”
Section: Allosteric Modulation Of the Glp-1r Occurs Within A Single Rmentioning
confidence: 84%
“…In contrast, BETP, a small molecule GLP-1R modulator that does not bind the ECD, signals through a distinct mechanism that appears to function in parallel to GLP-1 (Refs. 32, 34, and 35) and that induces a distinct ("biased") downstream signaling response (34). Surprisingly, the ability of BETP but not GLP-1 to stimulate GLP-1R signaling depended on Cys-347 in ICL3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Boc5 and S4P largely, but not completely, displaced labeled GLP-1 from GLP-1R and may, therefore, also interact with the TMD (27). In contrast, the pyrimidine BETP (31) was not competed by exendin(9 -39) or GLP-1 and is, therefore, thought to allosterically activate GLP-1R (31)(32)(33)(34). Recent work has demonstrated that BETP functions by forming covalent adducts with Cys-347 in the intracellular loop 3 (ICL3) of GLP-1R, which may mimic a physiological covalent modification (35).…”
Section: Small Molecule Glp-1r Modulators Mimic Endogenous Peptide Homentioning
confidence: 99%
“…Recent work demonstrated that coincubation with BETP markedly enhances the activity of truncated metabolite of GLP-1(7-36)NH 2 , i.e., GLP-1(9-36)NH 2 , at the GLP-1R (Wootten et al, 2012). Here, we took advantage of the latter procedure to test whether the GSH conjugate of BETP (i.e., M1) retains positive allosteric modulator properties of BETP.…”
Section: Resultsmentioning
confidence: 99%
“…4-(3-(Benzyloxy)phenyl)-2-(ethylsulfinyl)-6-(trifluoromethyl)pyrimidine (compound B or BETP) (Fig. 1) is one such analog that has been identified as a positive allosteric modulator of the naturally occurring inactive GLP-1 metabolite, GLP-1(9-36)NH 2 , while showing little modulation of the active, circulating form, i.e., GLP-1(7-36)NH 2 (Sloop et al, 2010;Wootten et al, 2012). Likewise, the insulinotropic effect of oxyntomodulin [glucagon(1-37)], a low-affinity full agonist of the GLP-1R, was also markedly enhanced in the rat i.v.…”
Section: Introductionmentioning
confidence: 99%